Penentuan Interval Penggantian Komponen Mesin Pengayakan BatuBara Dengan Metode Age Replacement - Ahmad Badriez Zamani; Moch. Nuruddin; Said Salim Dahda (Fakultas Teknik, 2023)
PT X is a manufacturing industry company, where one of the machines used is the Coal Sieving Machine. Krena machines are used continuously meneurs, so regular maintenance is required. This machine has two critical components, namely the gearbox component and the V-Belt Conveyor. During this time, PT. X carries out suboptimal repair activities, namely technicians only replace components when there is damage that can cause downtime. The purpose of this study is to determine alternative time intervals for machine component replacement and analyze the implementation of appropriate preventive maintenance to reduce the total downtime that occurs with the age replacement method approach. The results of the study obtained the replacement time interval for Gearbox components at intervals of 14 days while on the V-Belt Conveyor components, namely at intervals of 16 days. The total cost of replacing gearbox components due to damage amounted to Rp. 3,286,955 and for the calculation of the total maintenance cost (TC*) of Rp. 56,549,187. As for the replacement of V-Belt Conveyor components due to damage amounting to Rp. 3,101,104 and for the calculation of the total maintenance cost (TC*) of Rp. 58,260,118.